2013
DOI: 10.1109/mpul.2013.2271686
|View full text |Cite
|
Sign up to set email alerts
|

A clinical roadmap for brain-neural machine interfaces: trainees' perspectives on the 2013 international workshop

Abstract: Brain-neural machine interfaces (BNMIs) are systems that allow a user to control an artificial device, such as a computer cursor or a robotic limb, through imagined movements that are measured as neural activity. They provide the potential to restore mobility for those with motor deficiencies caused by stroke, spinal cord injury, or limb amputations. Such systems would have been considered a topic of science fiction a few decades ago but are now being increasingly developed in both research and industry. Worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Indeed, consensus at the NRI workshop on Clinical Brain–Neural Machine Interface Systems held at the Houston Methodist Research Institute in Spring 2013 1 showed that although neuroprostheses, neurally controlled exoskeletons, and other types of BMI systems have achieved success in a handful of investigative studies, translation of closed‐loop neuroprosthetic devices from the laboratory to the market is challenged by gaps in the scientific data regarding long‐term device reliability and safety, uncertainty in the regulatory market and reimbursement pathways, as well as patient‐acceptance challenges that impede their fast and effective translation to the end user (Liew et al 2013).…”
Section: Figurementioning
confidence: 99%
“…Indeed, consensus at the NRI workshop on Clinical Brain–Neural Machine Interface Systems held at the Houston Methodist Research Institute in Spring 2013 1 showed that although neuroprostheses, neurally controlled exoskeletons, and other types of BMI systems have achieved success in a handful of investigative studies, translation of closed‐loop neuroprosthetic devices from the laboratory to the market is challenged by gaps in the scientific data regarding long‐term device reliability and safety, uncertainty in the regulatory market and reimbursement pathways, as well as patient‐acceptance challenges that impede their fast and effective translation to the end user (Liew et al 2013).…”
Section: Figurementioning
confidence: 99%
“…One of the first meetings to address these challenges and discuss potential solutions to accelerate the translation of clinical BMI systems to the end-user was held at The Methodist Hospital Research Institute in February 2013 (http://bmiconference.org/), which brought together about 100 leaders from government, academia, medical centers, industry, foundations, and the patients. A preliminary report [66] reported on key challenges facing the translation of neuroprosthetic technology, including gaps in the scientific data regarding long-term device reliability and safety, uncertainty in the regulatory, market and reimbursement pathways, as well as patient-acceptance challenges that impede fast and effective translation to the end-user. It is clear that a regulatory roadmap and associated guidelines will facilitate innovation and investment in BMI device development, and translation of this neurotechnology to patients in need.…”
Section: Future Directionsmentioning
confidence: 99%
“…The 2013 International Workshop on Clinical Brain--Neural Machine Interface (BMI) Systems was held on February 25–27, 2013 at the Houston Methodist Research Institute, Houston, Texas [1]–[3]. The purpose of the workshop was to identify and discuss challenges and potential solutions leading to the development and deployment of interface systems based on neural activity in clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the workshop was to identify and discuss challenges and potential solutions leading to the development and deployment of interface systems based on neural activity in clinical applications. A review of the workshop written by participating trainees can be found in [1]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation